2011
DOI: 10.1186/1743-7075-8-33
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids intake in the Mexican population. Results of the National Nutrition Survey 2006

Abstract: BackgroundThere is growing evidence that quality, rather that quantity of fat is the determinant of cardiovascular risk. The objective of the study is to describe quantitatively the intake and adequacy of fatty acid classes among the Mexican population aged 5-90 years from a probabilistic survey.MethodsDietary intake of individual and classes of fatty acids was computed from the dataset of the 2006 Mexican National Health and Nutrition Survey (ENSANUT2006), collected by a food frequency questionnaire. Adequacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
44
5
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 32 publications
(35 reference statements)
9
44
5
9
Order By: Relevance
“…These findings are in concordance with those of Ramirez et al (2009) from the same population. These authors reported that persons living in northern Mexico had the lowest intake of fruit and vegetables in the country (31) . In our study we observed that rural inhabitants had the highest compliance with recommendations for the CPI, except for the consumption of fruit and vegetables.…”
Section: Discussionmentioning
confidence: 97%
“…These findings are in concordance with those of Ramirez et al (2009) from the same population. These authors reported that persons living in northern Mexico had the lowest intake of fruit and vegetables in the country (31) . In our study we observed that rural inhabitants had the highest compliance with recommendations for the CPI, except for the consumption of fruit and vegetables.…”
Section: Discussionmentioning
confidence: 97%
“…37 El bajo consumo de fibra pudiera explicarse por un consumo deficiente de frutas y verduras en la dieta de los niños, como ya se ha mencionado en un estudio previo. 38 En otro orden de ideas, tomando en consideración el porcentaje con el que contribuye cada grupo de alimentos al consumo total de energía, destaca que la menor proporción de niños que consumió frutas y verduras así como alimentos ricos en vitamina A se concentró entre los que pertenecen a hogares en inseguridad alimentaria moderada y severa. En este contexto, estudios realizados en Estados Unidos han evidenciado que los grupos de alimentos que aportan una mayor cantidad de vitaminas, minerales y fibra, principalmente frutas y hortalizas, son más costosos que aquéllos que aportan azúcares, grasas y energía.…”
Section: -34unclassified
“…Likewise, the sum of lauric and myristic acids was lower than 20% in all formulas; however, two stage 3 formulas showed very low values (<2%; Nan 3 and Progress Gold 3). Notably, the content of DHA and AA was insufficient in an important number of products; this is alarming since the intake of omega-3 and omega-6 fatty acids is very low in Mexican population as previously described by Ramirez-Silva et al [21]. In the succeeding section, formulas are grouped according to their nutrition stage to perform a more exhaustive analysis.…”
Section: Discussionmentioning
confidence: 99%